Impedance matching and power recovery in response to coil misalignment in wireless power transmission - Ardhenta, Lunde; Hodaka, Ichijo; Yamaguchi, Kazuya; Hirata, Takuya (Institute of Advanced Engineering and Science, 2025)
The improper alignment of the coils between the transmitter and receiver has a significant impact on wireless power transfer. If designers carefully calculate the parameters of inductance, capacitance, coupling coefficient, and working frequency and precisely implement these parameters into actual components, the system can optimize power transfer. However, it is evident that such a precise realization is often unachievable. This paper proposes a symbolic condition to maintain significant power despite the misalignment of transmitter and receiver coils. These symbolic conditions constrain parameters by simplifying some variables. This matching condition develops in the inequality of coupling coefficient, working frequency and quality factor, which are a crucial reference for maintaining power transfer. This condition is considered an additional one to the well-known impedance matching condition.